The Impact of Business Intelligence On the Performance Indicators of the Strategic Map: Extracted Researchتأثير ذكاء الأعمال على مؤشرات الأداء في الخريطة الاستراتيجية: بحث مستخلص - Ali, Aree (The Arab Journal of Administration, 2023)
The study dealt with important variables for the present business organizations represented in business intelligence and indicators of the strategic map. Where business intelligence is one of the modern topics that have been widely popular in many organizations, as it makes the organization in continuous communication with customers, knowing their requirements, producing and providing appropriate goods and services to them, which increases the organization’s opportunities for competition. On the other hand, the strategic map is a model for clarifying the organization’s strategy as it aims to facilitate the translation of the strategy into a practical reality and achieve linkage between the work of employees and the overall objectives of the organization and identifies performance indicators in four areas represented in the financial, marketing, internal operations, and of learning and growth. The study aimed to determine the nature of the relationship between business intelligence and its reflection on the extent of adoption of the strategic map indicators. The study was built on a number of main hypotheses that reflect the relationship between intelligence and its impact on the extent of adoption of the strategic map indicators. To test the validity of these hypotheses, a number of retail stores belonging to international business organizations operating within the city of Dohuk and Erbil were chosen to conduct the field side of the study. The final study sample included (100) workers in the researched organizations, and the data were analyzed using a set of statistical methods using the program ) Spss-18-For ( windows. The most important results of the study were the existence of a significant positive correlation between the variables of the study and a positive significant relationship between them. The study concluded that some recommendations were presented to enhance the levels of business intelligence and indicators of the strategic map in the surveyed organizations.